2021
DOI: 10.3390/nu13041269
|View full text |Cite
|
Sign up to set email alerts
|

The Immunomodulatory Effects of Honey and Associated Flavonoids in Cancer

Abstract: Honey has exerted a high impact in the field of alternative medicine over many centuries. In addition to its wound healing, anti-microbial and antioxidant properties, several lines of evidence have highlighted the efficiency of honey and associated bioactive constituents as anti-tumor agents against a range of cancer types. Mechanistically, honey was shown to inhibit cancer cell growth through its pro-apoptotic, anti-proliferative and anti-metastatic effects. However, the potential of honey to regulate anti-tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 109 publications
1
32
0
Order By: Relevance
“…Studies revealed that honey may exhibit chemopreventive and therapeutic effects against several cancer forms. Several investigations highlight that honey may display anticancer potential involving different molecular mechanisms, such as cell cycle arrest, apoptosis induction, and activation of mitochondrial pathways, with immunomodulatory and anti-inflammatory effect [ 3 , 50 , 51 , 52 ]. ZH has been widely investigated for its healing properties, especially against microbial infectious diseases [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies revealed that honey may exhibit chemopreventive and therapeutic effects against several cancer forms. Several investigations highlight that honey may display anticancer potential involving different molecular mechanisms, such as cell cycle arrest, apoptosis induction, and activation of mitochondrial pathways, with immunomodulatory and anti-inflammatory effect [ 3 , 50 , 51 , 52 ]. ZH has been widely investigated for its healing properties, especially against microbial infectious diseases [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, despite the many hypotheses on the mechanisms for the numerous beneficial effects, honey's full potential has started to be unlocked only recently, with more comprehensive characterisations of its physicochemical composition (as described in Section 2 of this paper), and the further investigation of the medical activity of natural bioactive compounds also found in honey [6][7][8][9][10][11][12][13][14][15]. Honey has been shown to possess beneficial properties with diverse applications in otorhinolaryngology [16,17], respiratory tract diseases [18,19], cardiovascular diseases [20][21][22], metabolic disorders [23][24][25][26], oncology [27,28]. However, the focus of this review is on the use of honey in the management and treatment of skin disease and in particular wounds of various natures, exploring the possible mechanisms by which honey may enhance skin regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Phenolic acids, which can be found in many plant species, are phenylpropanoids with an aromatic ring attached to a three-carbon side chain. Many biological activities, such as antioxidant, antimicrobial, antihepatotoxic, antiosteoporotic, antiulcer, immunomodulatory, and apoptotic activities, are attributed to phenolic acids [ 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. One class of phenolic acids—hydroxycinnamic acids—is greatly abundant in food and regarded to account for about one-third of dietary phenolic compounds [ 8 ].…”
Section: Resultsmentioning
confidence: 99%